COVID-Twitter-BERT: A natural language processing model to analyse COVID-19 content on Twitter - Müller, Martin; Salathé, Marcel; Kummervold, Per E. (Frontiers in Artificial Intelligence, 2023)
In this work, we release COVID-Twitter-BERT (CT-BERT), a transformer-based model, pretrained on a large corpus of Twitter messages on the topic of COVID-19. Our model shows a 10–30% marginal improvement compared to its base model, BERT-LARGE, on five different classification datasets. The largest improvements are on the target domain. Pretrained transformer models, such as CT-BERT, are trained on a specific target domain and can be used for a wide variety of natural language processing tasks, including classification, question-answering and chatbots. CT-BERT is optimised to be used on COVID-19 content, in particular from social media